Gut microbiota and chronic obstructive pulmonary disease: a Mendelian randomization study - Wei, Yi; Lu, Xuechao; Liu, Chao (Frontiers in Microbiology, 2023)
Abstract: Background: A growing number of studies implies a strong association between gut microbiota and chronic obstructive pulmonary disease (COPD). However, the causal impact between gut microbiota and COPD remains unclear. As a result, we used a two-sample Mendelian randomization (MR) method to investigate the connection between gut microbiota and COPD in this study. Methods: The largest available genome-wide association study (GWAS) of gut microbiota was obtained from the MiBioGen consortium. Summary-level dataset for COPD were obtained from the FinnGen consortium. The main analysis method for determining the causal link between gut microbiota and COPD was inverse variance weighted (IVW). Subsequently, pleiotropy and heterogeneity tests were performed to determine the reliability of the results. Results: IVW method identified 9 bacterial taxa associated with risk of COPD. Class Actinobacteria (P = 0.020), genus Allisonella (P = 0.024), genus Coprococcus2 (P = 0.002) and genus Oscillospira (P = 0.018) were protective against COPD. In addition, order Desulfovibrionales (P = 0.011), family Desulfovibrionaceae (P = 0.039), family Peptococcaceae (P = 0.020), family Victivallaceae (P = 0.012) and genus Marvinbryantia (P = 0.017) were associated with a higher risk of COPD. No pleiotropy or heterogeneity were found. Conclusion: According to the findings of this MR analysis, a causal relationship exists between certain gut microbiota and COPD. New insights into the mechanisms of COPD mediated by gut microbiota are provided.